Implementation of The People's Service Program for Land Certificate in City of Tebing Tinggi - Pandapotan Damanik (IHSA Institute, 2021)
The government through BPN has made a program for land registration, which can be marked by the Larasita Program. With the implementation of the Larasita Program in the City of Tebing Tinggi, it is expected to increase the registration of property rights to land in the City of Tebing Tinggi. In its implementation, the Larasita Program has not been successful in increasing the registration of land ownership rights in the City of Tebing Tinggi. This study uses an empirical juridical approach, with the research location in Tebing Tinggi City. A juridical approach is used to analyze various laws and regulations related to the implementation of the Larasita Program in the City of Tebing Tinggi. An empirical approach is used to analyze the law which is seen as the behavior of the people of Tebing Tinggi City who register property rights to land through the Larasita Program, which is patterned in people's lives, which always interact and relate in social aspects.Based on the research, it is known that the Larasita Program is regulated in the LBPNRI Perkaban. There are internal and external factors that influence the Larasita Program in the City of Tebing Tinggi, and efforts have been made by the BPN in the City of Tebing Tinggi so that the Larasita Program can be successful in increasing the registration of land rights in the City of Tebing Tinggi.